Disentangling the contribution of the transboundary out-flow from the Asian continent to Tokyo, Japan. (1st October 2021) - Shimada, Kojiro; Mizukoshi, Manatsu; Chan, Chak K.; Kim, Yong Pyo; Lin, Neng-Huei; Matsuda, Kazuhide; Itahashi, Syuichi; Nakashima, Yoshihiro; Kato, Shungo; Hatakeyama, Shiro
Abstract: We assessed the contribution of transboundary air pollutants (TAPs) transported from China to Tokyo using the Pb(0.5(2.5<Dp < 10) index. We conducted intensive observations over four seasons during 2014–2015 and analyzed ionic components and thirteen elements in size-segregated aerosols collected at the top of a 30-m-high tower in a hilly forested area of the Field Museum Tamakyuryo (FM Tama), in a western suburb of Tokyo. In order to evaluate if the Pb(0.5(2.5<Dp < 10) ratio can be applied in Tokyo as the megacity, the annual average concentration of Pb at Cape Hedo, Kumamoto city, on the west side of Japan, was higher than that of Pb at Tokyo, on the east side; this result indicates that TAPs affect western Japan more than eastern Japan. We inferred the main source of Cu to be braking abrasion from cars at local scale on the basis of its enrichment factor and size distribution. From the Pb(0.5(2.5<Dp < 10) ratio and sulfate concentration, we inferred that the highest contribution of TAPs to the total mass concentration in Tokyo occurred in spring, when TAPs accounted for 55%, 72%, and 53% of the total mass concentration in the 0.1 < Dp < 0.5, 0.5 < Dp < 1, and 1 < Dp < 2.5 fractions, respectively. These results can contribute to assessment of TAPs in Tokyo. Graphical abstract: Image 1 Highlights: Identifying transboundary air pollutants in Tokyo was developed. Air mass was classified by chemical components, satellite and air quality model information. We inferred the contribution of transboundary air pollutants in Tokyo was 60%.